COMPARATIVE ANATOMICAL ANALYSIS OF EREMURUS ROBUSTUS AND E. TIANSCHANICUS GROWING IN THE ZAILIYSKIY ALATAU (ҚазҰУ хабаршысы. Экология сериясы, 2026)
The genus Eremurus (Asphodelaceae) represents one of the characteristic groups of the flora of Central Asia, distinguished by its ornamental value and practical significance in traditional medicine. However, the anatomical structure of its representatives under different ecological conditions remains insufficiently studied. The aim of this study was to conduct a comparative anatomical analysis of two species occurring in the Ile Alatau. Leaves and stems were used as study material, fixed in 70% ethanol and processed according to a standard histological protocol with paraffin embedding. Transverse sections 40 µm thick were prepared using a rotary microtome and examined by light microscopy with digital photodocumentation. Morphometric measurements included epidermal thickness, the size of palisade mesophyll, the diameter of water-storage cells in the leaf, as well as epidermal thickness, the size of primary cortex cells, and the diameter of water-storage cells in the stem. The study revealed that both species exhibit xeromorphic traits: a uniseriate epidermis with a thickened cuticle and sunken stomata, the presence of palisade mesophyll and water-storage cells in the leaves, and well-developed vascular bundles. In the stem, a dense epidermis, a distinct primary cortex, and collateral vascular bundles with water-storage cells were observed. Interspecific differences were also identified: the first species had larger primary cortex cells and water-storage elements, reflecting a water-accumulating adaptive strategy, while the second exhibited a more developed palisade mesophyll and greater stability in tissue dimensions, indicating a photosynthetic type of adaptation. The results contribute to a better understanding of the ecological plasticity and intraspecific variability of Eremurus in the mountainous and foothill ecosystems of Central Asia.Key words. Asphodelaceae, Adaptations, Anatomy, Eremurus, Ile Alatau.